Vbodne rane trebuha - analiza 10-letne serije - Ivanecz, Arpad (Acta medico-biotechnica, 2011)
Purpose: The incidence of abdominal stab wounds (ASWs) is high in some regions of the world. In general, the dilemma of the workup of these patients remains unsolved. We analyzed the epidemiological and demographical characteristics, and presented the strategy of the workup of patients with ASWs. Our results were compared with those from the literature. Methods: In this retrospective study we reviewed the records of all patients with ASWs treated between 1997 and 2007 at University Medical Center - Maribor (Maribor, Slovenia). In patients with circulatory instability and in those with signs of peritoneal irritation, explorative laparotomy was done immediately. The indication for laparotomy was also given in all asymptomatic patients with penetration across the peritoneum as evidenced by exploration of ASWs. Results: Fifty-six patients with ASWs were treated in our institution; 51 had a single stab wound and were asymptomatic on hospital admission. There were 23 explorative laparotomies for ASWs, the mean number being 2 per year (range, 0-4 per year). The liver and small intestine were the most often injured. Perioperative complications occurred in 13% of 23 stabbed patients. Late morbidity (after hospital discharge) was 26%. No patient from the present study died as a result of ASWs or perioperative complications. Conclusion: The incidence of ASWs in our part of the country is much lower than in many other urban regions in the world. The selective conservative approach to ASWs is advantageous and this is reflected in a lower number of unnecessary laparotomies. An experienced surgical team, continuous access to imaging systems and invasive procedures, and the possibility of immediate surgical intervention are necessary for this approach. If these conditions are not fulfilled, then the traditional approach- laparotomy - may be safer if there is evidence of a penetrating abdominal stab wound.
Keywords: abdominal stab wounds; laparotomija; laparotomy; trebuh; vbodne rane